2008
DOI: 10.1080/0972060x.2008.10643638
|View full text |Cite
|
Sign up to set email alerts
|

Cymbopogon citratus(DC) Stapf Volatile Oil from South - West, Nigeria

Abstract: Chemical analysis of the volatile oil of Cymbopogon citratus and its antibacterial effects were investigated. Chemical analysis of the C. citratus oil was determined using Gas Chromatograph-Mass Spectrometry technique. Out of 47 peaks (representing 97.36 % of the total oil), 37 constituents were identified representing 90.86 % of the total oil constituents. The major constituents were geranial (40.9 %), neral (29.7 %), myrcene (11.3 %), linalool (1.7 %) and geranylacetate (1.6 %). The oil was examined against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Also the oil has the tendency to polymerise because of high content (5-25 %) of the monoterpene β-myrcene in the oil, thus deteriorating the quality of the oil 1 . This oil has been the subject of several studies by many researchers from different countries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . According to a recent review a total of 158 compounds were identified in this oil by several research groups from different countries 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Also the oil has the tendency to polymerise because of high content (5-25 %) of the monoterpene β-myrcene in the oil, thus deteriorating the quality of the oil 1 . This oil has been the subject of several studies by many researchers from different countries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . According to a recent review a total of 158 compounds were identified in this oil by several research groups from different countries 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of these factors however, most reports of chemical compositions indicated that the oil consists mainly of citral, a mixture of two stereoisomeric monoterpene aldehydes. This is particularly the case in most reports of oil composition from Nigeria (Onawunmi et al, 1984;Adeleke et al, 2001;Owolabi et al, 2008). In this wise, citral has remained the key compound in evaluating the quality of LGO (Onawunmi, 1989;Bassolé et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…No originário de Marrocos, os principais constituintes encontrados foram geranial (39,8%) e neral (32%) (Il Idrissi et al, 1993), enquanto que naqueles originários da Zâmbia e do Zimbabue foram encontrados geranial, neral e mirceno em diferentes proporções porém com expressiva predominância dos dois primeiros (Chisowa et al, 1998;Chagonda et al, 2000). No óleo essencial de uma amostra da Nigéria foram encontrados geranial (40,9%), neral (29,7%), mirceno (11,3%), linalool (1,7%) e acetato de geranila (1,6%) (Owolabi et al, 2008).…”
Section: Introductionunclassified